Tax certified individual auditors and effective tax rates - Lisa Frey (Business Research, 2018)
This study examines how the appointment of tax certified individual auditors is associated with reported effective tax rates of corporate clients. The study uses a unique German institutional setting which makes it possible to track individual auditors that are also certified tax consultants and sign the audit opinion. Empirical results indicate that tax certified individual engagement partners are associated with higher effective tax rates. Further tests reveal that this association also exists for individual parent company financial statements and that it is stronger when tax confirmation services are provided to the audit client. My findings enhance the understanding of the role of individual auditors.
Keywords: M41; M42; H26; 650; Tax certified individual auditor; Effective tax rate; Knowledge spillover